2020
DOI: 10.1155/2020/3091564
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Asymptomatic Bacteriuria and Antibiotic Susceptibility Patterns of Bacterial Isolates among Cancer Patients and Healthy Blood Donors at the University of Gondar Specialized Hospital

Abstract: Background. Urinary tract infections are the common types of infections in the community and health care settings. Despite the widespread availability of antibiotics, urinary tract infection remains a worldwide therapeutic problem. It is a continuous and significant problem in cancer patients. Methods. A hospital-based comparative cross-sectional study was conducted on 240 study participants from January to June 2019. Sociodemographic data were collected by a predesigned questionnaire and midstream urine sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
4
12
1
1
Order By: Relevance
“…Many demographic factors and clinical features were analyzed as risk factors for bacteriuria in cancer patients in this study, however, no evidence was found to support the association between bacteriuria and demographic and clinical features of the cancer patients (P > 0.05). Correspondingly, in other studies [ 24 26 ] reported that neither of the factors and clinical features mentioned in our study had no effect on the occurrence of bacteriuria.…”
Section: Discussionsupporting
confidence: 75%
“…Many demographic factors and clinical features were analyzed as risk factors for bacteriuria in cancer patients in this study, however, no evidence was found to support the association between bacteriuria and demographic and clinical features of the cancer patients (P > 0.05). Correspondingly, in other studies [ 24 26 ] reported that neither of the factors and clinical features mentioned in our study had no effect on the occurrence of bacteriuria.…”
Section: Discussionsupporting
confidence: 75%
“…Urinary tract infection (UTI) is one of the most common infections among cancer patients due to their prolonged immunosuppression, complex cancer treatment and catherization [ 18 , 19 ]. Treating UTI in cancer patients is clinically challenging as many cancer patients are at high risk of AMR due to long-term chemotherapies, depressed immune systems and repeated use of antibiotics to prevent and/or treat infections [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria such as Escherichia coli, Enterococcus faecalis Klebsiella species, Proteus mirabilis, Pseudomonas aeruginosa and Streptococcus agalactiae are some of the causative agent of urinary tract infections (UTI). Blockage of the urinary tract, catheter usage, deficiency in oestrogen, genetic predisposition and sexual intercourse are predominant risk factors for urinary tract infection (Tigabu et al, 2020). Asymptomatic bacteriuria (ASB) is the detection of 10 5 CFU/ml of one or more 46 bacterial species, irrespective of pyuria, in a urine specimen from a pregnant women patient without any symptoms of a urinary tract infection (UTI) (Willey et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Blockage of the urinary tract, catheter usage, deficiency in oestrogen, genetic predisposition and sexual intercourse are predominant risk factors for urinary tract infection (Tigabu et al, 2020). Asymptomatic bacteriuria (ASB) is the detection of 10 5 CFU/ml of one or more 46 bacterial species, irrespective of pyuria, in a urine specimen from a pregnant women patient without any symptoms of a urinary tract infection (UTI) (Willey et al, 2020). The relatively upsurge of ASB in pregnancy, the consequences encountered by the women and their pregnancies, avoidance of treatment with undesired outcomes, screening and treatment of ASB in pregnancy with justification.…”
Section: Introductionmentioning
confidence: 99%